2022
DOI: 10.1097/hjh.0000000000003298
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and diastolic left ventricular function in children with primary hypertension: a systematic review and meta-analysis

Abstract: Objective:Evaluation of left ventricular function provides early evidence of target-organ damage in children with primary hypertension. We performed a systematic review and meta-analysis of left ventricular systolic and diastolic function in children and adolescents with primary hypertension.Methods:Literature search was performed in PubMed database and out of 718 articles (published between 2000 and 2021) 22 studies providing comparison of left ventricular function parameters between children with primary hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
(340 reference statements)
0
5
0
Order By: Relevance
“…Bubenek et al [ 188 ] reported a strong association between NNMT expression, serum MNA levels, and the onset and progression of peripheral arterial occlusive disease. Interestingly, NNMT expression has been found to be positively associated with LDL levels and negatively associated with HDL levels, both of which are factors associated with cardiovascular disease [ 189 , 190 , 191 ].…”
Section: Research Progress On Nnmt In Aging-related Diseasesmentioning
confidence: 99%
“…Bubenek et al [ 188 ] reported a strong association between NNMT expression, serum MNA levels, and the onset and progression of peripheral arterial occlusive disease. Interestingly, NNMT expression has been found to be positively associated with LDL levels and negatively associated with HDL levels, both of which are factors associated with cardiovascular disease [ 189 , 190 , 191 ].…”
Section: Research Progress On Nnmt In Aging-related Diseasesmentioning
confidence: 99%
“…Additionally, Bubenek et al ( Bubenek et al, 2012 ) reported a robust association between NNMT expression, serum MNAM levels, and the onset and progression of peripheral arterial occlusive disease. Notably, NNMT expression has been found to be positively correlated with LDL levels and negatively correlated with HDL levels, both of which are relevant factors in cardiovascular diseases ( Herfindal et al, 2020 ; Kornev et al, 2023 ; Rus et al, 2023 ). As shown in Figure 5 , left ventricular contractile dysfunction and arterial vascular disease are significant contributors to the development of hypertension, suggesting a potential pathway through which NNMT may influence hypertension.…”
Section: Study Progress Of Nnmt In Mets-related Diseasesmentioning
confidence: 99%
“…The significance of early life blood pressure (BP) elevation is well reflected by studies reporting that childhood BP tracks into adulthood and is associated with cardiovascular outcomes, including hypertension-mediated organ damage (HMOD) ( 2 4 ). The latter is already apparent in childhood, including changes in left ventricular and vascular structure and function ( 5 7 ). Moreover, evidence suggests that pediatric primary hypertension is not a condition characterized by elevated BP alone but represents a phenotype accompanied by changes in body composition, metabolic abnormalities, immune-inflammatory alterations and increased sympathetic activity ( 8 ).…”
Section: Introductionmentioning
confidence: 99%